2023
DOI: 10.1186/s12967-023-03970-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a novel prognostic signature based on mitochondria and oxidative stress related genes for glioblastoma

Abstract: Background Mitochondria represent a major source of reactive oxygen species (ROS) in cells, and the direct increase in ROS content is the primary cause of oxidative stress, which plays an important role in tumor proliferation, invasion, angiogenesis, and treatment. However, the relationship between mitochondrial oxidative stress-related genes and glioblastoma (GBM) remains unclear. This study aimed to investigate the value of mitochondria and oxidative stress-related genes in the prognosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Previous research has demonstrated that removing MRPL37 increases susceptibility to paclitaxel [24] . Cathepsin L (CTSL) is a mitochondrial stress response marker linked to mitochondrial oxidative stress [ 25 , 26 ]. CTSL, a cysteine protease, plays an important role in tumor cell resistance to chemotherapy and has been associated with radioresistance [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that removing MRPL37 increases susceptibility to paclitaxel [24] . Cathepsin L (CTSL) is a mitochondrial stress response marker linked to mitochondrial oxidative stress [ 25 , 26 ]. CTSL, a cysteine protease, plays an important role in tumor cell resistance to chemotherapy and has been associated with radioresistance [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple studies on the construction of a LASSO prognostic model for glioblastoma. Tong et al [19] proposed a prognostic model of mitochondria and oxidative stress-related genes, whereas Zhang et al [20] built a cuproptosis-related prognostic model, which can independently predict the prognosis of GBM patients. We also created a predictive model with a similar purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Other mitochondrial genes such as ABCC3, HOXA4, HOXC10, NNMT, and SCNN1B are typically increased in their expression as the grade of glioma and the higher expression of these genes have been associated with poor prognosis in LGG [56]. Other mitochondrial oxidative-stress-related genes including CTSL, TXNRD2, NUDT1, STOX1, and CYP2E1 have been reported differentially expressed with potential prediction accuracy of glioma [57]. CMC1, COX20, and UQCRB are other mitochondrial genes specifically involved in the prognosis of glioma [37].…”
Section: Discussionmentioning
confidence: 99%